2015
DOI: 10.1111/eea.12385
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affecting the behavior of Coenosia attenuata, a predator of Trialeurodes vaporariorum in tomato greenhouses

Abstract: Adults of the predatory fly Coenosia attenuata Stein (Diptera: Muscidae) catch their prey while in flight. I investigated this activity over two seasons in a tomato greenhouse naturally infested with Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae). The flight of C. attenuata individuals was affected by environmental factors and was increased in response to increases in temperature, the number of prey flights, and conspecific density. Predator and prey flights were distributed throughout the day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Temperature variation and deviation from the optimal temperature affect predation rates (Logan & Wolesensky, 2007;Bonsignore, 2016). To the best of our knowledge, the present study is the fi rst to provide insights into the effect of temperature on the functional response of N. tenuis.…”
Section: Discussionmentioning
confidence: 85%
“…Temperature variation and deviation from the optimal temperature affect predation rates (Logan & Wolesensky, 2007;Bonsignore, 2016). To the best of our knowledge, the present study is the fi rst to provide insights into the effect of temperature on the functional response of N. tenuis.…”
Section: Discussionmentioning
confidence: 85%
“…3 × 10 2 ). This figure is just above that calculated for fruit flies (D. virilis, 200 [30], D. melanogaster, 128 [31]) and considerably lower than the dragonfly (700-2400 [32]), highlighting the high viscous forces killer flies experience despite high success rates in the wild [33].…”
Section: Discussionmentioning
confidence: 66%
“…The flight of C. attenuata individuals was affected by environmental factors and was increased in response to increases in the number of prey flights [37]. Bonsignore (2016) found that predatory flights of adult C. attenuata comprised a small percentage (ca. 6%) of the total flights, with a predation success rate of 61% [37].…”
Section: Discussionmentioning
confidence: 99%
“…Adults of C. attenuata use mean flight speeds of 0.69 ms −1 , mean wingbeat frequency of 306, 19 Hz and acceleration of mean peak 9.3 ms −2 to intercept prey [36]. The flight of C. attenuata individuals is affected by environmental factors, adjusting in response to changes in temperature, the number of prey flights and conspecific density [37]. Therefore, wing damage will cause negative effects on the life of C. attenuata adults.…”
Section: Introductionmentioning
confidence: 99%